2021
DOI: 10.3892/etm.2021.9866
|View full text |Cite
|
Sign up to set email alerts
|

Role of HDAC6 inhibition in sepsis‑induced acute respiratory distress syndrome (Review)

Abstract: Acute respiratory distress syndrome (ARDS) induced by sepsis contributes remarkably to the high mortality rate observed in intensive care units, largely due to a lack of effective drug therapies. Histone deacetylase 6 (HDAC6) is a class-IIb deacetylase that modulates non-nuclear protein functions via deacetylation and ubiquitination. Importantly, HDAC6 has been shown to exert anti-cancer, anti-neurodegeneration, and immunological effects, and several HDAC6 inhibitors have now entered clinical trials. It has al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 88 publications
1
7
0
Order By: Relevance
“…Also pharmacological administration of an HDAC6 inhibitor given three hours after LPS challenge could significantly reduce the mortality. These experiments confirmed that HDAC6 plays a key role in sepsis and, in agreement with our results, literature data reported that HDAC6i ameliorate sepsis-induced ARDS by regulating both innate and adaptive immunity, preserving endothelial barrier function and attenuating pro-inflammatory gene transcription ( 70 , 100 , 101 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Also pharmacological administration of an HDAC6 inhibitor given three hours after LPS challenge could significantly reduce the mortality. These experiments confirmed that HDAC6 plays a key role in sepsis and, in agreement with our results, literature data reported that HDAC6i ameliorate sepsis-induced ARDS by regulating both innate and adaptive immunity, preserving endothelial barrier function and attenuating pro-inflammatory gene transcription ( 70 , 100 , 101 ).…”
Section: Discussionsupporting
confidence: 93%
“…It has been extensively shown that pan HDACi dampen pro-inflammatory and innate immune responses in pre-clinical models of sepsis ( 68 , 69 ). Interestingly, also HDAC6 is involved in sepsis and its inhibition improves survival in murine sepsis models ( 70 ). In agreement with this evidence, we observed that HDAC6 KO mice had a higher survival compared to wild type (WT) mice upon induction of septic shock by LPS ( Figure 3A ) .…”
Section: Resultsmentioning
confidence: 99%
“…The typical ones include ACY1215, 87 CAY10603 88 and tubastatin A. 79,89 However, the recent study conducted by our group evaluated an anthraquinone extracted from Rheum palmatum that shared the same mother nuclei with emodin, namely sennoside A (Sen A), and its effect on HDAC6, a decreased protein level of HDAC6, was observed in LPS plus ATP-stimulated macro-phages following Sen A incubation (data not shown). Since HDAC6 participates in the transportation of NLRP3 to the microtubule-organizing center where aggresome formation and autophagosomal degradation occurs, 81 it will be of interest to explore potential inhibitors which can interfere with this process.…”
Section: Small-molecule Compounds From Dietary Plants Alleviate Sepsi...mentioning
confidence: 99%
“…HDAC6 is a class IIb HDAC that is exclusively localized in the cytoplasm and directly associates with MT, α-tubulin being its preferred substrate (Hubbert et al, 2002;Matsuyama et al, 2002). As therapeutic potential of HDAC6 inhibition has been evaluated in cardiovascular, neurodegenerative diseases and cancers, recent studies have assessed the role of HDAC6 inhibition in endothelial dysfunction-derived ALI (Kovacs et al, 2018;Zhang et al, 2021). Initial studies showed the protective effects of HDAC6 inhibitors against thrombin-induced permeability in EC culture (Saito et al, 2011) and attenuation of LPS-induced ALI in mice (Ni et al, 2010).…”
Section: Histone Deacetylase 6: Microtubules-associated Deacetylase As a Therapeutic Target In Lung Injury Syndromesmentioning
confidence: 99%